«Green economy» as a way of future development of Kazakhstan - Granetsky, V.N.; Madiyarova, E.S.; Rakhimberdinova, M.U.; Karayilmazlar, E. (BUKETOV BUSINESS REVIEW, 2019)
In the article theoretical aspects of realization of the concept of «green economy» in the Republic of Kazakhstan are considered. The essence, content and basic principles of the «green economy» as a basis for stimulating the sustainable development of the national economy are difined. The key achievements of the «green economy» are considered: creation of «green» workplaces, creation of new «green» industrial branches, increase of high-tech workplaces, creation of ecological sustainable economy and beverage social development. Authors studied the potential problems of transformation of the Republic of Kazakhstan to a new «green» course of economic development. The conditions and tools for the transition to a green economy that will lead to the emergence of new economic opportunities are formulated. On the basis of the received results the characteristic and suggestions on improvement of ecological and economic policy in the Republic are given. The specific measures to reduce the costs of production of alternative energy sources are introduced.